The Life of William Carey, Shoemaker & Missionary - Smith, George, 1833-1919 (Salt Lake City, UT : Project Gutenberg, 2000)
"The Life of William Carey, Shoemaker & Missionary" by George Smith is a historical account written during the late 19th century. This biography chronicles the life of William Carey, from his humble beginnings as a shoemaker in England to becoming a pioneering missionary in India, where he significantly impacted both Christianity and local culture through his translations and educational efforts. At the start of the book, the author introduces William Carey$1 (Bs early life, highlighting his modest upbringing in Paulerspury, where he demonstrated an insatiable thirst for knowledge despite his lower-class status. Carey's experiences as a shoemaker and his fundamental transformations due to religious awakenings provide a foundation for his later work. The narrative sets the stage for Carey's journey, detailing his deep commitment to learning, his encounters with fellow religious figures, and the societal challenges he faced while cultivating his missionary ambitions. Ultimately, the opening paints a picture of a dedicated individual whose resolve to spread the Gospel would lead to substantial changes in India and beyond. (This is an automatically generated summary.)s
Release date is 2000-02-01
Produced by John Bechard. HTML version by Al Haines.
Keywords: Carey, William, 1761-1834; Missions -- India